Evaluation of Cusp Deflection in Teeth Restored with Various Manipulation Techniques and Types of Composite Restorations - Ahmed A. Alquzweeni1 , Mustafa Basim Al-Talqani2 , Marwah Safaa Ali3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study aim to evaluate and compare the deflection of premolar teeth cusps that filled incrementally withconventional composite (Universal Ceram X One Sphere TEC TM) and various types of bulk fill compositematerials (Kerr SonicFillTM3 , 3M FiltekTM Bulk Fill and Shofu Beautifil Bulk Fill). In this study 40 human,healthy maxillary first premolars were collected and large MOD cavity were prepared in them . Accordingto restorative materials, the teeth were haphazardly categorized in 4 groups (n=10 per group). Group I :The teeth were filled with SonicFill™3 Kerr composite, Group II : The teeth were filled with Filtek BulkFill, Group III : The teeth filled with Shofu Beautifil Bulk Fill composite, and Group IV : The Teeth werefilled with Dentsply Ceram X One Sphere TEC TM. By the aid of digital microscope intercuspal distance onthe tips of the cusps between two index reference points was measured pre preparation of the cavity , postpreparation, after 15 minutes of completion of fillings. The cuspal deflection was calculated by determinationof the changes in measurements. Inward cuspal deflection was occurred in all teeth after filling , minimalcuspal deflection reported in all study groups that filled with bulk fill filling in comparison with group IV thatfilled in layering technique with conventional composite. Greater cuspal deflection produced by BeautifilBulk Fill restorative in comparison with other groups. As a conclusion of this study that using of new bulkfilling restorative materials could dramatically minimize cuspal deflection.